UMPSA strengthens Industry-Academia Collaboration with WBL Implementation and Adjunct Professor appointments - Naqiah, Puaad (UMPSA, 2024)
KUANTAN, 15 July 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has further strengthened its collaboration with 29 industry partners through the signing of a memorandum of agreement (MoA) and a memorandum of understanding (MoU).